2019
DOI: 10.1177/1947603519847737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Viscosupplementation on Quality of Knee Joint Arthrokinematic Motion Analyzed by Vibroarthrography

Abstract: Objective To evaluate the influence of viscosupplementation on osteoarthritic knee arthrokinematics analyzed by VAG. It is considered that intra-articular hyaluronic acid injection may improve the function of synovial joints by recovery of friction-reducing properties of articular environment. Design Thirty-five patients with knee osteoarthritis (grade II according to the Kellgren-Lawrence system) and 50 asymptomatic subjects were enrolled in the study. Patients were analyzed at 3 time points: 1 day before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The methodological aspects of acoustic assessments, such as sensor placement and outcomes measures have not been thoroughly investigated allowing doubt in the technique to remain. For instance, for knee investigations, many studies [73,81,101] favour what may be called an open kinematic chain configuration [102] whereby participants sit in a chair and lift their legs in a repetitive fashion, perhaps with weights attached. This has the advantage of being able to vary the load on the joint and allow for the inclusion of participants with advanced degenerative conditions or injuries affecting the limitation of the range of motion in the joint.…”
Section: Resultsmentioning
confidence: 99%
“…The methodological aspects of acoustic assessments, such as sensor placement and outcomes measures have not been thoroughly investigated allowing doubt in the technique to remain. For instance, for knee investigations, many studies [73,81,101] favour what may be called an open kinematic chain configuration [102] whereby participants sit in a chair and lift their legs in a repetitive fashion, perhaps with weights attached. This has the advantage of being able to vary the load on the joint and allow for the inclusion of participants with advanced degenerative conditions or injuries affecting the limitation of the range of motion in the joint.…”
Section: Resultsmentioning
confidence: 99%
“…Both variability (VMS) and amplitude (R4) of representative signals are characterized by [18,38]. In turn, low spectral activity analyzed by summing spectral power of the VAG signal in two bands: 50-250 Hz (P1) and 250-450 Hz (P2) seems to be related with intact integrity of the superficial layer of hyaline cartilage and an efficient lubrication mechanism [37,45]. Nonetheless, in the present study we predominantly focused on the impact of the external load on the quality of PFJ arthrokinematic motion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cone-beam computed tomography (CBCT) showed that 20% of the patients improved the standard excursion of the mandibular head in both joints after treatment and it was also possible to confirm one of the main functions of the acid Hyaluronic acid (HA), which is the chondroprotective effect, with the improvement of the articular disc. This technique is also extensively studied in osteoarthritis of the knee, presenting several effects of HA on the synovial joint, such as the improvement of function by the recovery of the friction reducing properties of the articular environment, of the pain (15). Although the evidence for the use of intra-articular injections with HA in the knee OA is inconclusive and not recommended by the American Academy of Orthopedic Surgeons (AAOS) in clinical practice, the physician needs to present the benefits and the harmful of this possibility of treatment for patients (16).…”
Section: Discussionmentioning
confidence: 99%